EFEK ENDORPHIN MASSAGE TERHADAP PRODUKSI ASI IBU POST PARTUM - Juniekasari, Dian; Dwi Anjani, Arum; Yenny Marsela (Universitas Batam, 2022)
The Lancet Breastfeeding Series (2018) says directly that breast milk can prevent IMR because the effect of contamination is around 88%. the variable that drives the increase in the amount of breast milk is the influence of the mother and baby, in the influence of the mother, the thing that is very encouraging is the factor of the mother's vitalization and psychological well-being. The use of effects that do not use drugs to increase breast milk volume is the endorphin massage technique. Endorphins make the body feel fit and relaxed so as to minimize the stress felt on the mother. Stimulation of the back of the body by massaging is given to automatically bring up the effects of oxytocin. Endorphin massage has an important role in evidence in increasing the amount of breast milk in postpartum mothers. This study aims to see if there is an effect of endorphin massage on the increase in breast milk volume. The method used is a qualitative approach (library research) with a literature study research procedure or literature and quantitative with a simple quick survey method which is carried out in a random manner. The results showed that breast milk production carried out by endorphin massage had a more significant effect than no massage, so it can be determined that there is control of endorphin massage on the increase in the amount of breast milk in postpartum mothers. a convenient and efficient non-pharmacological option in dealing with breast milk production in postpartum mothers